Analisis Penentuan Nisbah Bagi Hasil Pembiayaan Musyarakah Pada PT Bank Syariah Mandiri - Dony Firmansyah Arizal Gustavo; Wirman Wirman (Peneliti.net, 2023)
The purpose of this research is to analyze the determination of profit sharing ratios for musyarakah financing at PT. Branch Office of Bank Syariah Mandiri Karawang. This study uses descriptive research with a study case design. The data sources used in this study are direct data sources (primary data) and indirect (secondary data). In this study primary data was obtained through interviews with collaborators regarding musyarakah funds, while the secondary data in this study may be in the form of books, reports related to musyarakah contract transactions, as well as other sources related to research. The methods used are observation, interviews and documentation.